The Enforcement of Business Competition Law by the Police: An Indonesian Experience - Disemadi, Hari Sutra; Roisah, Kholis (Lentera Hukum, 2019)
In Indonesia, the Commission for the Supervision of Business Competition or Komisi Pengawas Persaingan Usaha (KPPU) is granted the power according to Law Number 5 of 1999 but such a power cannot be optimally implemented. KPPU often experiences difficulties and obstacles in the process of enforcing business competition law due to a large number of business actors and uncooperative witnesses so that this hinders the process of examining cases. In particular, KPPU has lack of cooperation of involved parties during the inspection process. However, the KPPU in carrying out its authority can include the role of the Indonesian police to assist in the process of enforcing business competition law. This paper shows that the role of the Indonesian police in the enforcement of business competition law can be initiated during the investigation process if the KPPU requests assistance to present the reported party, witnesses, and expert witnesses. Until the decision is issued by the KPPU, investigators can follow up with relevant individuals that may have cases that contain criminal aspects. Keywords: Business Competition Law, the Commission for the Supervision of Business Competition, Indonesian Police